[RETRACTED] Corporate governance, capital structure, and performance in family and non-family firms - Tyara Dwi Putri; Purbo Jadmiko; Neva Novianti; Giralda Triyani Arista (DIJB (Diponegoro International Journal of Business))
This article was retracted due to the following reasons. A retraction announcement will be made in Vol 6 (1), 2023.